PKK deletion in basal keratinocytes promotes tumorigenesis after chemical carcinogenesis. (22nd November 2017) - Chen, Luojing; Hayden, Matthew S; Gilmore, Elaine S; Alexander-Savino, Carolina; Oleksyn, David; Gillespie, Kathleen; Zhao, Jiyong; Poligone, Brian
Abstract: Squamous cell carcinoma (SCC) of the skin is a keratinocyte malignancy characterized by tumors presenting on sun-exposed areas with surgery being the mainstay treatment. Despite advances in targeted therapy in other skin cancers, such as basal cell carcinoma and melanoma, there have been no such advances in the treatment of SCC. This is partly due to an incomplete knowledge of the pathogenesis of SCC. We have recently identified a protein kinase C-associated kinase (PKK) as a potential tumor suppressor in SCC. We now describe a novel conditional PKK knockout mouse model, which demonstrates that PKK deficiency promotes SCC formation during chemically induced tumorigenesis. Our results further support that PKK functions as a tumor suppressor in skin keratinocytes and is important in the pathogenesis of SCC of the skin. We further define the interactions of keratinocyte PKK with TP63 and NF-κB signaling, highlighting the importance of this protein as a tumor suppressor in SCC development. Abstract : The protein kinase C-associated kinase (PKK) is a novel tumor suppressor in skin keratinocytes. Keratinocyte-specific deletion of PKK leads to increased proliferation in keratinocytes and tumor growth in a mouse model of squamous cell carcinoma of the skin in humans.